AB0389 BIOSIMILAR ETANERCEPT VERSUS ORIGINATOR: RESULTS FROM A LONGITUDINAL PROSPECTIVE MONOCENTRIC STUDY. (June 2019) - Lucchetti, Ramona; Ceccarelli, Fulvia; Perricone, Carlo; Truglia, Simona; Miranda, Francesca; Franco, Manuela DI; Riccieri, Valeria; Scrivo, Rossana; Scavalli, Antonio Sili; Spinelli, Francesca; Alessandri, Cristiano; Valesini, Guido; et al.
Abstract : Background: The introduction of TNF inhibitors have revolutionized the outcome of patients affected by Rheumatoid Arthritis (RA). In the last years, pharmaco-economic implications determined the introduction of biosimilar as alternative to originator biological drugs. Phase I and head-to-head phase III clinical studies demonstrated pharmacokinetic equivalence and comparability in terms of efficacy, safety, immunogenicity and tolerability. However, biosimilar drugs demonstrated some differences related to charge and glycosylation, not influencing the function and the ability to bind the soluble TNF. To date, very few data are available concerning the use of biosimilar drugs in a real-life setting. Results from DANBIO registry suggested a lower retention rate in RA patients switchers from Etanercept originator (ETA) to biosimilar (SB4) versus the historic ETA cohort and higher in comparison with historic SB4 patients (1). Objectives: To compare the efficacy of ETA versus SB4 in a cohort of RA patients in a real life setting. Methods: In this monocentric case-control prospective study, we consecutively enrolled RA patients starting ETA or SB4 treatment from 2015. RA diagnosis was made according with ACR/EULAR 2010 criteria (2). Data were collected and entered into a standardized, computerized, electronically filled-in form. We included patient demographics, date of diagnosis, comorbidities and previous and concomitant medications. The clinical evaluation included the count of swollen and tender joints and the patient's and physician's global disease assessment based on a visual analogue scale (VAS; range, 0 to 100 mm). Disease activity was measured according to the disease activity score in 28 joints (DAS28ESR) (3). The patients were asked to fill in the Health Assessment Questionnaire (HAQ). All the patients were evaluated at the beginning of treatment (T0) and after 4 (T1) and 12 months (T2). Clinical response to treatment was evaluated by using EULAR criteria (4). Results: We evaluated 35 RA patients treated with SB4 (M/F 2/33; median age 63 years, IQR 21; median disease duration 108 months, IQR 138) and 40 with ETA (M/F 5/35; median age 60.5 years, IQR 20; median disease duration 102 months, IQR 141). Biologic drug was prescribed as first-line biological treatment in 71.4% of SB4 cohort and in 80.0% of ETA. At T0 no significant differences were observed among the two groups in terms of DAS28ESR [SB4 median 4.6 (IQR 1.8), ETA 4.3 (IQR 1.9), p=ns] and HAQ [SB4: median 1 (IQR 1.05), ETA median 1 (IQR 0.85), p=ns]. In both groups we observed a significant reduction of DAS28 values at T1 (BS4 p=0.01; ETA p<0.0001) and T2 (SB4 p=0.0007; ETA p= 0.0002; Figure 1A ). When evaluating the remission rate (DAS28ESR<2.6) at T1, we observed a significant higher rate in ETA (53.8%) versus SB4 (26.7%; p= 0.0002; Figure1B ). No differences were found after 12 months of treatment. Conclusion: The results of our study confirmed in a real-life setting the efficacy of SB4 in RA patients, as demonstrated by the significant reduction of DAS28ESR values after 4 and 12 months of treatment, similarly to ETA. Nonetheless, ETA seems to be able to induce a remission status earlier than SB4. References: [1] Glintborg B, et al. Ann Rheum Dis. 2018 [2] Aletaha D, et al. Arthritis Rheum. 2010 [3] Anderson JK, et al. Arthritis Care Res. 2011 [4] van Gestel AM, et al. Arthritis Rheum. 1996 Disclosure of Interests: Ramona Lucchetti: None declared, Fulvia Ceccarelli: None declared, Carlo Perricone Speakers bureau: BMS; Lilly, Celgene, Sanofi, Simona Truglia: None declared, Francesca Miranda: None declared, Manuela Di Franco: None declared, Valeria Riccieri: None declared, Rossana Scrivo: None declared, Antonio Sili Scavalli: None declared, francesca spinelli: None declared, cristiano alessandri: None declared, Guido Valesini: None declared, Roberta Priori: None declared, fabrizio conti: None declared